2023
DOI: 10.21037/tp-22-679
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and a prognostic nomogram based on the SEER database for hepatoblastoma, hepatocellular carcinoma, and embryonal sarcoma among children and adolescents

Abstract: Background: Hepatoblastoma (HB), hepatocellular carcinoma (HCC), and embryonal sarcoma (ES) are the three main types of liver tumors in children and adolescents. At present, epidemiological knowledge and predictors of these three liver tumor types in multi-ethnic populations are limited. This study aimed to outline the clinical features and construct a prognostic nomogram for these tumors, which can contribute to the prediction of dynamic overall survival probability during the follow-up period. Methods: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Nomograms are renowned for their capacity to offer precise, personalized prognostic estimates, exceeding conventional tumor staging standards. Nevertheless, previous studies have only conducted limited investigations to explore the potential of developing a nomogram-based prediction model for precise forecasts of the OS of patients with HB ( 20 , 21 ). In addition, previous studies have not shown specially tailored nomograms to forecast cancer-specific survival (CSS) within patients with HB.…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms are renowned for their capacity to offer precise, personalized prognostic estimates, exceeding conventional tumor staging standards. Nevertheless, previous studies have only conducted limited investigations to explore the potential of developing a nomogram-based prediction model for precise forecasts of the OS of patients with HB ( 20 , 21 ). In addition, previous studies have not shown specially tailored nomograms to forecast cancer-specific survival (CSS) within patients with HB.…”
Section: Introductionmentioning
confidence: 99%